(untitled) (African Journal of Biomedical Research, 2020)
This study was conducted to determine the prevalence, in relation to gender, age and risk factors associated with Schistosoma haematobium infections among primary school children in Jimeta-Yola. Each child was administered a semi-structured questionnaire to collect socio-demographic data. Urine samples were collected from 150 pupils for microscopic analysis for the detection of S. haematobium eggs. The prevalence of S. haematobium eggs in Yelwa Primary School, showed that females had the highest prevalence rate with 12 (40.0%) infection while male had a prevalence rate of 8 (17.78%) infection. The infection in relation to age showed that the age range 8-10 years had the highest infection with 11 (44.0%), the age range 14> years had the least prevalence with 2 (10.00%). The prevalence in Limawa Primary School, showed that males had a prevalence rate of 9 (19.15%) infection while female had a prevalence rate of 7 (25.00%) infection. The infection in relation to age showed that the age range <8 years had the highest infection with 7 (28.00%), while nothing was recorded in the age 14 > years. In general, the prevalence rate of urinary schistosomiasis infection among primary school children in jimeta-yola, adamawa state is fairly low with a prevalence of 24.0 % among active school children. No significant difference was found between gender, age, source of water, and urinary schistosomiasis Keywords: Schistosoma haematobium; Prevalence; Gender; Age; Risk factors; Yola;. *Author for correspondence: E-mail: vandiphilips@yahoo.com Received: June 2018; Accepted: May, 2019 Abstracted by: Bioline International, African Journals online (AJOL), Index Copernicus, African Index Medicus (WHO), Excerpta medica (EMBASE), CAB Abstracts, SCOPUS, Global Health Abstracts, Asian Science Index, Index Veterinarius INTRODUCTION Communities around water bodies have high risk of parasitic infections, water plays an important role in the life cycle of parasites, and humans cannot live without water. (WHO, 2014). These worms are released by snails. The Schistosomiasis is one of the most widespread of all human parasitic diseases, it ranks second only to malaria in terms of its socioeconomic and public health importance in tropical and subtropical areas (Chitsulo, 2000). Schistosomiasis is a major public health problem affecting over 200 million people worldwide (WHO, 2011). As a mainly rural, often occupational disease, schistosomiasis principally affects people who are unable to avoid contact with natural water sources, either because of their profession (agriculture, fishing) or because of lack of reliable water for drinking, washing and bathing (Ekpo et al., 2010). Irrigation farmers and fishermen are among those that are more prone to the infection. There are repeated cases of these parasites in humans, especially children. (Tetteh- Quarcoo et al., 2013), since children frequently have contact with water either for domestic purpose or for fun. Increased population movement seems to enhance the spread of the disease, and schistosomiasis is now occurring www.ajbrui.org Schistosomiasis, also known as snail fever or bilharzia, is a disease caused by parasitic flatworms called Schistosomes